Cross section measurements of deuteron induced nuclear reactions on natural titanium up to 34 MeV. (September 2015) - Duchemin, C.; Guertin, A.; Haddad, F.; Michel, N.; Métivier, V.
Abstract: Experimental cross sections for deuteron induced nuclear reactions on natural titanium were measured, using the stacked-foil technique and gamma spectrometry, up to 34 MeV with beams provided by the ARRONAX cyclotron. The experimental cross section values were monitored using the nat Ti(d, x) 48 V reaction, recommended by the IAEA. The excitation functions for nat Ti(d, x) 44 m, 46, 47, 48 Sc are presented and compared with the existing ones and with the TALYS 1.6 code calculations using default models. Our experimental values are in good agreement with data found in the literature. TALYS 1.6 is not able to give a good estimation of the production cross sections investigated in this work. These production cross sections of scandium isotopes fit with the new Coordinated Research Project (CRP) launched by the International Atomic Energy Agency (IAEA) to expand the database of monitor reactions. Abstract : Highlights: Deuteron induced reactions on natural titanium up to 34 MeV. Monitor reactions database (CRP IAEA). Experimental values determined using the stacked-foil technique. Comparison with the TALYS code version 1.6.